Disseminated cutaneous sporotrichosis in a patient with AIDS: report of a case - Carvalho,Miriam Tomoko Mitsuno (2002)
We describe a case report of disseminated cutaneous sporotrichosis as the initial presentation of AIDS in a 24-year-old HIV-positive male patient. He presented multiple ulcerated skin lesions distributed over the face, thorax, legs and arms. Biopsy of one of the cutaneous lesions was suggestive of sporotrichosis and culture isolated Sporothrix schenckii. Itraconazole was started and the lesions progressively resolved after 15 days of medication. The patient was discharged with this medication but he did not return for follow-up. He died three months later in another hospital. Therapy of sporotrichosis in HIV-infected patients remains unclear and the response to therapy is variable. Itraconazole is highly concentrated in the skin and is one of the options for treatment of disseminated sporotrichosis.